Validity and analysis of the Diabetes Injection Device Preference Questionnaire (DID-PQ) - Kristina S. Boye; Louis S. Matza; Brooke M. Currie; Karin S. Coyne (SpringerOpen, 2020)
Abstract Introduction The Diabetes Injection Device Preference Questionnaire (DID-PQ) was designed to assess patient preference between two non-insulin injection devices. In a recent crossover study, people with type 2 diabetes (T2D) completed the DID-PQ after performing mock injections with two non-insulin injection devices. The purpose of the current analysis was to use these data to assess construct validity of the DID-PQ and demonstrate one way to test whether there is a significant preference for one injection device over another. Methods Data were from an open-label, multicenter, randomized, crossover study assessing preference between the dulaglutide and semaglutide injection pens. In addition to the 10-item DID-PQ, people with T2D completed a global item assessing overall preference. DID-PQ responses were compared to the global preference item (percent agreement, Gwet's AC1, prevalence-adjusted and bias-adjusted Kappa [PABAK]). For each item of the DID-PQ, a two-sided binomial test assessed whether the difference in preference was statistically significant. Results The sample included 310 participants (48.4% female; mean age = 60.0). The DID-PQ had minimal missing data. There was strong concordance (percent agreement > 78%) between the global preference item and all DID-PQ items except item 6, which assesses preference related to needle size (59.7%). The Gwet AC1 and PABAK statistics also indicated strong agreement between the global preference item and all DID-PQ items except item 6. There was a statistically significant difference (p < 0.0001) in preference on every DID-PQ item, with more participants preferring the dulaglutide device. Discussion Patient preference has been recommended as a "major factor driving the choice of medication" in a consensus report by the American Diabetes Association and the European Association for the Study of Diabetes. Current findings suggest that the DID-PQ may be a useful tool for providing insight into preferences of people with T2D using non-insulin injectable medication.